Direct Measurement of Dynamics in Road Bridges Using a Bridge Weigh-In-Motion System - Eugene J. OBrien; Arturo González; Jason Dowling; Aleš Žnidarič (The Baltic Journal of Road and Bridge Engineering)
A method is presented of measuring a bridge’s characteristic allowance for dynamic interaction in the form of Assessment Dynamic Ratio. Using a Bridge Weigh-in-Motion system, measurements were taken at a bridge in Slovenia over 58 days. From the total observed traffic population, 5-axle trucks were extracted and studied. The Bridge Weigh-in-Motion system inferred the static weights of the trucks, giving each measured event’s dynamic increment of load. Theoretical simulations were carried out using a 3-dimensional vehicle model coupled with a bridge plate model, simulating a traffic population similar to the population measured at the site. These theoretical simulations varied those properties of the 5-axle fleet that influence the dynamic response; simulating multiple sets of total (dynamic + static) responses for a single measured static strain response. Extrapolating the results of these theoretical simulations to a 50-year Assessment Dynamic Ratio gives similar results to those obtained by extrapolating the data measured using the Bridge Weigh-in-Motion system. A study of the effect of Bridge Weigh-in-Motion system errors on the predictions of Assessment Dynamic Ratio is conducted, identifying a trend in the Bridge Weigh-in-Motion calculations of maximum static response. The result of this bias is in turn quantified in the context of predicting characteristic maximum total load effect.